1983
DOI: 10.1111/j.1745-9125.1983.tb00266.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Pornography in a Southern Community

Abstract: ABSTRACT* * * The Supreme Court has determined that obscene speech should not be protected under the First Amendment, but an unambiguous definition of obscenity is required if negative legal sanctions are to be enforced without jeopardizing due process. According to current guidelines, a media presentation of sexually explicit materials must exceed limits of sexual candor to be defined obscene. However, establishing such limits requires articulation of a normative standard for a specified population—a populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Gunther (1995), Hense and Wright (1992), and Rojas et al (1996) all found women are more likely to endorse censorship of pornography. And men expressed more favorable views toward sexual candor in mass media presentations than did women (Herrman & Bordner, 1983). Bird (1997), however, found no significant gender differences in willingness to censor hate speech, while D. M. McLeod, Eveland, and Nathanson (1997) detected no differences in endorsement of censorship of violent and misogynic rap lyrics.…”
Section: Gendermentioning
confidence: 90%
“…Gunther (1995), Hense and Wright (1992), and Rojas et al (1996) all found women are more likely to endorse censorship of pornography. And men expressed more favorable views toward sexual candor in mass media presentations than did women (Herrman & Bordner, 1983). Bird (1997), however, found no significant gender differences in willingness to censor hate speech, while D. M. McLeod, Eveland, and Nathanson (1997) detected no differences in endorsement of censorship of violent and misogynic rap lyrics.…”
Section: Gendermentioning
confidence: 90%
“…Religiosity has been found to be positively associated with support for censorship (e.g., Fisher, Cook, & Shirkey, 1994;Herrman & Bordner, 1983;Lambe, 2004;Thompson, Chaffee, & Oshagan, 1990). Previous research has shown a negative association between intrinsic religiosity and tolerance of film portrayals of homosexuals, but demonstrated no significant association between extrinsic religiosity and tolerance of such film portrayals (Detenber, Cenite, Ku, Ong, Tong, & Yeow, 2007).…”
Section: Religious Beliefsmentioning
confidence: 94%
“…Studies on attitudes toward pornography and attitudes resulting from pornography find that the majority of the general public objects to pornography and believes pornography promotes negative attitudes toward women (Herman and Bordner 1983;Kirkpatrick and Zurcher 1983;Bart et al 1985; War on Pornography 1985; Davis and Smith 1986;Pornography 1986). However, a majority of the general public also opposes censorship of pornographic magazines and X-rated videocassetr.es; and many people believe pornography provides educational information on sex.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Also, many survey studies found that respondents have both positive and negative attitudes towards pornography (Davis and Smith, 1986;Pornography 1986;War on Pornography 1985;Bart, Freeman, and Kimball, 1985;Herman and Bordner 1983;Kirkpatrick and Zurcher 1983).…”
mentioning
confidence: 97%